Islamisasi Ilmu dan Ilmuisasi Islam: Polemik dalam Integrasi Islam dan Sains: POLEMIC IN THE INTEGRETION OF ISLAM AND SCIENCE - Achmad Reza Hutama Al Faruqi Reza; Mujamil Qomar; Rif’at Husnul Ma’afi Rif’at; Sayyid Muhammad Indallah Sayyid (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2024)
This article aims to explore the meaning of Islamization of Contemporary Science and Scientization of Islam (Pengilmuan Islam), as well as a paradigm comparison of the two. Both have a role in integrating Islam and science, which has the aim of eliminating the dichotomy between science and Islam. So, both of these come forward to play a role in this goal. The study of the integration of Islam and science is very thick and has many styles in Indonesia in particular, such as: Pohon Ilmu, Integrasi Interkoneksi Sarang laba-laba, Twins Tower, Roda Pedati, Model Intan Berlian Ilmu, islamization of contemporary science, scientization of Islam and so on. However, the author only examines the two styles, namely Islamization and scientization of Islam. This research uses library research with the method of comparative analysis. So that it produces several points, including that the islamization of science and the scientification of Islam have the same goal, namely to integrate religion and science, so that there is no dichotomy between the two.  However, there are differences in the paradigm of the two, Islamization of science is said to be mentioned from context to text, but the author does not agree with that opinion, rather agreeing that Islamization of science is a way of Islamizing or returning the meaning of science to the original, so that there is no mixture with secular science. While the Islamization of science is reading an object from text to context, in the author's opinion this is more to answer the wonders of the text in the Qur'an. From the conclusion, if all styles or types of integration in Indonesia agree and join, then the scientific tradition in Islam will be more advanced and developed. Keywords: Islamization, Scientization, Science, Al-Attas, Al-Faruqi, Kuntowijoyo.